The Photographer's Eye A Graphic Guide : instantly understand composition & design for better digital photos - Freeman, Michael, 1945- (Routledge, 2014)
Michael Freeman's unrivalled compositional advice, first presented in the bestelling The Photographer's Eye, is explained in a new and deliberately visual manner in The Photographer's Eye: A Graphic Guide . Photography is a visual language in itself, and therefore lends perfectly to visual explanation. Drawing on his long professional experience as an editorial photographer, Michael Freeman shows exactly how images work by using a beguilingly simple technique. His unique style of illustration (which he does himself ) deconstructs photographs in a way that is clear, elegant and thoughtful. The information in this book can be absorbed in minutes, but last you a lifetime.